Child Adoption and Conflicts of Jurisdiction: A Comparative Analysis of the Public Court and the Islamic Court of Surakarta - Muhammad Latif Fauzi; Mohammad Harazi Al Abyari Fauzi (Universitas Islam Sultan Agung, 2023)
The adoption of Muslim children is one of the familial issues in Indonesia. At the law level, the Indonesian law authorizes two judicial institutions, namely Islamic and public courts, to handle the case. Here, conflicts of jurisdiction occur obviously and, as a consequence, the parties have the choice to decide which court to request based on their wishes. This article answers the question of why and what the consequences of conflicts of jurisdiction are in the case of the adoption of Muslim children? The study found that two judicial institutions both accepted and examined cases of the adoption of Muslim children. However, there is a difference in the legal consequences. If the adopted child is to be treated as a biological child and can inherit, the application is filed to a public court. On the contrary, if the child is to be maintained, it is an Islamic court that judges. In the case of family lineage (nasab), both the courts do not break the ties of the adopted child with his/her biological parents, including the right of guardianship.